Evidence for the B-0 -> p(p)over-barK*(0) and B+->eta K-c*(+) decays and study of the decay dynamics of B meson decays into p(p)over-barh final states - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2007)
With a sample of 232×106 Υ(4S)→BB̄ events collected with the BABAR detector, we study the decays of B mesons to pp̄h final states, where h=π+, KS0, K*0, or K*+. We report evidence for the B0→pp̄K*0 decay, with a branching fraction (1.47±0. 45(stat)±0.40(syst))×10-6, and for the B+→ηcK*+ decay, with the branching fraction of B(B+→ηcK*+) ×B(ηc→pp̄)=(1.57-0.45+0.56(stat)-0.36+0.46(syst)) ×10-6, and provide improved measurements of the branching fractions of the other modes of this type. We also report the measurements of the charge asymmetry consistent with zero in the B+→pp̄π+, B0→pp̄K*0, and B+→pp̄K*+ modes. No evidence is found for the pentaquark candidate Θ+ in the mass range 1.52 to 1.55GeV/c2, decaying into pKS0, or the glueball candidate fJ(2220) in the mass range 2.2